Technical assessment of a stand-alone hybrid renewable system for energy and oxygen optimal production for fishes farming in a residential building using HOMER pro - Wulfran Fendzi Mbasso; Serge Raoul Dzonde Naoussi; Reagan Jean Jacques Molu; Kenfack Tsobze Saatong; Salah Kamel (Cleaner Engineering and Technology, 2023)
Electricity holds both economic significance and strategic importance in many regions globally. Persistent challenges related to electricity generation, encompassing aspects like availability, quality, and cost, have impeded the progress of nations for an extended period. While conventional electrochemical storage systems have been the benchmark, they are plagued by issues such as high expenses, technical limitations in power output, and restricted storage capacity. Power generation facilities come with their own array of problems, including noise pollution, environmental impacts, and suboptimal performance, exacerbating the existing concerns of reliability and maintenance. To navigate the path of sustainable global development amidst a sharp upswing in energy consumption, it becomes imperative to foster innovative energy solutions. Independent renewable energy systems (RES) represent a promising avenue for reshaping the prevailing reliance on conventional power grids. The Hybrid Renewable Energy System (HRES) deserves careful calibration, particularly considering the considerable load fluctuations and the need for cost efficiency. The study considers a standalone HRES in a residential area on Manoka Island, where fish farming is a primary activity. This dwelling exhibits a daily electricity consumption averaging at 9.28 kWh, with peak demand hitting 0.88 kW. To evaluate the suitability of the Hybrid Optimization Model for Electric Renewable (HOMER) program, the study investigates the optimal energy generation mix for both sustaining the fish farming industry and fulfilling the energy requirements of the chosen building. The optimization process identifies four key parameters that undergo thorough assessment in this analysis. Delving into the specifics, the study attains an impressive renewable fraction (RF) of 92.5% and achieves a Deficit of Power Supply Probability (DPSP) of 0%. Furthermore, the production of 50 kg of O2 and the emission of 1.69 kg of carbon annually prove adequate for constructing a reliable and environmentally sound energy system. In a broader sense, this research serves as a compelling case study, elucidating the concept of hybrid energy systems within the framework of eco-friendly and sustainable power generation. The study not only underscores the substantial potential of RES for the country but also constitutes a significant stride for researchers active in this field.